2016
DOI: 10.1149/2.0201603jss
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Patterned Porous Low-kDielectrics: Surface Sealing and Residue Removal by Wet Processing/Cleaning

Abstract: The results described in this paper first demonstrate key differences between a plasma-exposed blanket porous dielectric sample and a patterned structure in terms of surface sealing induced by the patterning plasma using ellipsometric porosimetry characterization. While the blanket CVD organosilicate glass (nominal k-value = 2.4, ∼20% of porosity) surface was sealed by the C 4 F 8 /CF 4 -based plasma, the surface of the analogous patterned structure of 45 nm 1/2 pitch was found to be completely open after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Typically, in the Ti 2p region, the high intensity peak at lower BE side (459.1 eV) can be assigned to the Ti 2p 3/2 component, while the high BE peak at 464.8 eV is due to the Ti 2p 1/2 component. 23,24 As already discussed in our previous publication, 18 the binding energy of these peaks gives a clear evidence that the surface of the TiN layer has been oxidized to TiO 2 , most likely during the opening of the TiN layer as well as during the patterning of the OSG layer. The thickness of the TiO 2 surface layer is estimated to be significantly thinner than 5 nm, as an additional but weak signal from TiN was also detected at a lower BE, ∼455.2 eV.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Typically, in the Ti 2p region, the high intensity peak at lower BE side (459.1 eV) can be assigned to the Ti 2p 3/2 component, while the high BE peak at 464.8 eV is due to the Ti 2p 1/2 component. 23,24 As already discussed in our previous publication, 18 the binding energy of these peaks gives a clear evidence that the surface of the TiN layer has been oxidized to TiO 2 , most likely during the opening of the TiN layer as well as during the patterning of the OSG layer. The thickness of the TiO 2 surface layer is estimated to be significantly thinner than 5 nm, as an additional but weak signal from TiN was also detected at a lower BE, ∼455.2 eV.…”
Section: Resultssupporting
confidence: 64%
“…This behavior/characteristic was also observed for similar types of residues generated on a stack with OSG 2.4 as the dielectric. 18 The results shown in both Tables also confirmed that the TiN HM still remained at the surface. In general, the oxygen concentrations for all samples were significantly higher for the case with PET.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In contrast to the F1s spectra, very similar Ti2p spectra were recorded regardless of the TOA's within the range of 22-78 deg., which in turn confirms the previous statement. The binding energies and the shape of the Ti2p spectra suggest that several types of Ti compounds are present at the surface, including TiO 2 , TiN, and TiFx [3,4]. The presence of the latter is strongly supported by the observed F1s spectrum as discussed above.…”
Section: Resultsmentioning
confidence: 57%